In vivo and In vitro PPAR-y Activation Decreases M1-Macrophage Polarization and Improves Liver Ischemia Reperfusion Injury. (July 2018) - Linares, Ivan; Bartczak, Agata; Farrokhi, Kaveh; Kollmann, Dagmar; Kaths, Moritz; Hamar, Matyas; Urbanellis, Peter; Ganesh, Sujani; Adeyi, Oyedele; Yip, Paul; Selzner, Markus; Selzner, Nazia
Abstract : Background: M1-Macrophage polarization has been studied as a potential target to decrease inflammatory response in sepsis and inflammation related diseases. Its role in the setting of inflammatory response during liver ischemia reperfusion injury is unknown. Material a nd Methods: First, for in vitro experiments mouse peritoneal macrophages (PM) were stimulated with LPS+INFy to achieve M1-polarization. PMs received Rosiglitazone (RGZ-PPARy-agonist) or vehicle (Ctrl) 1hr before and then together with LPS+INFy and were incubated for 24hrs. For in vivo experiments, the groups underwent partial liver ischemia (70% of liver) and received RGZ or vehicle 24hr and 1hr prior to reperfusion. Liver samples were taken prior and following reperfusion (BL, 1hr, 6hr and 24hr) and were analyzed for apoptosis and necrosis with TUNEL and H&E staining, respectively. In vitro and In vivo (Liver) M1-macrophage polarization was evaluated by intracellular nitric oxide (NO) production and assessed with fluorescence (RFU-Relative fluorescence units) and flowcytometry, (MFI-Mean Fluorescence Intensity), respectively. Results: In vitro PPARy activation resulted in a significant reduction of NO production (M1-polarization) in the RGZ vs Ctrl group at 24hrs after stimulation (67238±6580 RFU vs 101310±7552 RFU, p< 0.01)(A ). In vivo PPARy activation prior to reperfusion significantly reduced NO production (M1-Kupffer cell polarization) in the RGZ vs Ctrl group at 6hr (1469±340 MFI vs 3069±779 MFI, p< 0.01) and 24hr (762±340 MFI vs 1074±198 MFI, p=0.04) following reperfusion (B ). TUNEL staining analysis showed significant reduction in the RGZ vs Ctrl group at 6hr after reperfusion (26.40±2.93 vs 50.13±8.29%; p=0.04). H&E staining revealed almost 50% reduction in the degree of necrosis in RGZ vs Ctrl group (26.66±4.78 vs 45.62±4.57%; p=0.03)(C ). Conclusion: PPAR-y activation prior to reperfusion improves the deleterious effect of liver reperfusion injury by decreasing M1-macrophage polarization. Figure. No caption available.